Poltekkes Kemenkes Malang’s Organizational Response In Facing The Implementation of Performance-Based Remuneration System (A Case Study on Public Service Institution within Resource Dependence Theory Perspective andNew Institutional Sociology) - Rahayu, Mintarsih Puji; Djamhuri, Ali; Rosidi, Rosidi (Universitas Negeri Malang, 2018)
This study is aimed at revealing the organizational response of Polkesma in facing pressure on the implementation of remuneration system and the way to continue the sustainability of remuneration system through Resource Dependence Theory and New Institutional Sociology perspective.This research uses post positive paradigm with qualitative approach and case study research strategy. The results showedthat the Organizational response which was initially shown in the form of Acquiesce met regulatory compliance (coercive isomorphism). In addition to the Acquiesce, the Polkesma showed a compromising response towards institutional pressure through the initiative to develop performance appraisal system by following the institution that had successfully applied (mimetic isomorphism) and used consultant service (normative isomorphism) to develop Key Performance Indicator (KPI). Efforts to continue the sustainability of Polkesma remuneration system were done by optimizing the escalation of main educational income, asset utilization, the principle of